Circulating Thrombomodulin: Release Mechanisms, Measurements, and Levels in Diseases and Medical Procedures - Boron, Mallorie; Hauzer-Martin, Tiffany; Keil, Joseph; Sun, Xue-Long (TH Open, 2022)
Thrombomodulin (TM) is a type-I transmembrane protein that is mainly expressed on endothelial cells and plays important roles in many biological processes. Circulating TM of different forms are also present in biofluids, such as blood and urine. Soluble TM (sTM), comprised of several domains of TM, is the major circulating TM which is generated by either enzymatic or chemical cleavage of the intact protein under different conditions. Under normal conditions, sTM is present in low concentrations (<10 ng/mL) in the blood but is elevated in several pathological conditions associated with endothelial dysfunction such as cardiovascular, inflammatory, infection, and metabolic diseases. Therefore, sTM level has been examined for monitoring disease development, such as disseminated intravascular coagulation (DIC), sepsis and multiple organ dysfunction syndrome in patients with novel coronavirus disease 2019 (COVID-19) recently. In addition, microvesicles (MVs) that contain membrane TM (MV-TM) have been found to be released from activated cells which also contribute to levels of circulating TM in certain diseases. Several release mechanisms of sTM and MV-TM have been reported, including enzymatic, chemical, and TM mutation mechanisms. Measurements of sTM and MV-TM have been developed and explored as biomarkers in many diseases. In this review, we summarize all these advances in three categories as follows: (1) release mechanisms of circulating TM, (2) methods for measuring circulating TM in biological samples, and (3) correlation of circulating TM with diseases. Altogether, it provides a whole picture of recent advances on circulating TM in health and disease.
Keywords: circulating thrombomodulin; COVID-19; endothelial cell; microvesicle; sepsis; soluble thrombomodulin; thrombomodulin; vascular damage